Transformasi Digitalisasi Pemasaran UMKM di Kampung Parugpug Kidul Desa Cijambe Kabupaten Sumedang : Peran Inovasi Mahasiswa Kuliah Kerja Nyata (KKN) dalam Edukasi, Mentoring, dan Penguatan Branding Produk Lokal: Pengabdian - Ira Amelia Putri; M. Rizqi Ilhami; Nabila Fauziyah; Rahma Novianty Suntana; Repa Rahmawati; Michelle Dwi Artha Sewidjaja; Indy Auliya; Sultan Fadhilah Hilmiqas; Rekian Faza Mahendra; Azka Mugni Almumtaz; Ramaditya Rahardian (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Digital transformation is the key for MSMEs to grow and develop in today's modern era. The service program carried out by students to help MSMEs increase product visibility and branding through digital marketing. This program was carried out for one month with a focus on developing MSMEs through marketing digitalization including workshop seminars, mentoring, and the formation of village marketing teams. The results of the program show that the digitalization of MSME marketing has an impact on increasing digital literacy, as well as online marketing capabilities. The MSME marketing digitalization implementation program in Cijambe Village is able to increase digital understanding, business skills, and competitiveness of MSME players, while ensuring sustainability through the village marketing team.